1985
DOI: 10.1002/ana.410170302
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory myopathies: Part 1

Abstract: The inflammatory myopathies have diverse clinical and pathological features and multiple etiologies. Some are confined to a single muscle or group of muscles (e.g., orbital myositis and localized nodular myositis) while others are diffuse. Infective forms may be due to viral, bacterial, fungal, protozoal, or parasitic organisms. Viruses may cause acute self-limited forms of myositis and have been isolated from muscle in some cases of acute rhabdomyolysis and inclusion body myositis. They have also been implica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(34 citation statements)
references
References 153 publications
2
31
0
1
Order By: Relevance
“…In our study, onset age was 32 years. It is reported that females outnumber males by 2:1 [13,14]. We reported this in male patient.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In our study, onset age was 32 years. It is reported that females outnumber males by 2:1 [13,14]. We reported this in male patient.…”
Section: Discussionsupporting
confidence: 55%
“…The cutaneous lesions usually precede the onset of weakness by 3 to 6 months, [6] however, Pearson [11] has described one case, with skin involvement for 13 years. It is known that DM has a bimodal age distribution: one peak occurs in children between 5-14 yr of age and a second, larger peak occurs between 45-64 yr of age [13,14]. In our study, onset age was 32 years.…”
Section: Discussionmentioning
confidence: 54%
“…Characterization of this group of pathologies is based on its pattern of muscle involvement, the presence of associated clinical manifestations, histopathological findings, response to treatment and prognosis. [4][5][6] This is a rare disease that predominantly affects females, at a proportion of 2:1, and which has an incidence of 3.2/ 1,000,000 children and adolescents/year in the United…”
Section: Introductionmentioning
confidence: 99%
“…Proximal muscle weakness and inflammatory infiltrates within the skeletal muscle characterize polymyositis (PM). When myositis is accompanied by characteristic skin lesions, it is called dermatomyositis (DM) [1][2][3][4] . The skin manifestations include a heliotrope rash (blue-purple discoloration) on the upper eyelids with edema, a flat red rash on the face and upper trunk, and erythema of the knuckles accompanied by a raised, violaceous scaly eruption (Gottron's sign).…”
mentioning
confidence: 99%
“…The incidence of PM, DM and inclusion-body myositis is approximately 1 in 100,000 3,5 . The cause of those diseases is still ignored, but the existence of genetic factors and autoimmune mechanisms is known 1,2,4,6 . Viral and bacterial infections as well as some drugs can also be related with the etiology of the inflammatory myopathies, but this type of condition needs to be distinguished from the idiopathic form being discussed 4,[6][7][8][9][10] .…”
mentioning
confidence: 99%